Methylated polycyclic aromatic hydrocarbons and/or their metabolites are important contributors to the overall estrogenic activity of polycyclic aromatic hydrocarbon–contaminated soils. (6th November 2017) - Lam, Monika M.; Engwall, Magnus; Denison, Michael S.; Larsson, Maria
Abstract: In the present study 42 polycyclic aromatic compounds (PACs) were investigated for their estrogenic potential using the VM7Luc4E2 transactivation assay. Relative potencies were determined for mass‐balance analysis. In addition, compounds were tested in combination with the estrogen receptor (ER) antagonist ICI182, 780 (ICI) and the aryl hydrocarbon receptor antagonist/CYP1A1 inhibitor α‐naphthoflavone. Luciferase induction and CYP1A1‐dependent ethoxyresorufin‐O‐deethylase (EROD) activity were measured to assess whether the estrogenic activity was elicited by the compound itself and/or by its metabolites. Relative potencies ranged between 10 −7 and 10 −4 . The ability of ICI to decrease luciferase activity stimulated by all compounds indicated that the induction responses were ER‐dependent. The aryl hydrocarbon receptor antagonist/CYP1A1 inhibitor α‐naphthoflavone decreased luciferase induction and EROD activity by several compounds, including the methylated chrysenes, suggesting that metabolites of these chemicals contributed to ER activation. Several PACs, such as acridine and its derivatives, appear to directly activate the ER. Furthermore, extracts of soils from industrial areas were examined using this bioassay, and estrogenic activity was detected in all soil samples. Mass‐balance analysis using a combination of relative potencies and chemical analysis of the samples suggested that polycyclic aromatic hydrocarbons (PAHs) and alkylated PAHs, such as 1‐ and 3‐methylchrysene, are important contributors to the overall estrogenic activity. However, these results revealed that a considerable proportion of the estrogenic activity in the soil remained unexplained, indicating the presence of other significant estrogenic compounds. Environ Toxicol Chem 2018;37:385–397. © 2017 SETAC Abstract : Developed relative potency factors for VM7luc4E2 transactivation assay in the present study were used in mass‐balance analysis to investigate estrogenic activity of PAH‐contaminated soil.